1997
DOI: 10.1161/01.cir.95.2.371
|View full text |Cite
|
Sign up to set email alerts
|

Transmyocardial Laser Revascularization

Abstract: We found different stages of wound healing in human nonresponder myocardium after TMR, resulting in scarred tissue that displayed capillary network and dilated venules without evidence of patent and endothelialized laser-created channels. Experimental studies are necessary to analyze the morphological basis for TMR-mediated effects in human responder myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0
1

Year Published

1999
1999
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(19 citation statements)
references
References 16 publications
0
18
0
1
Order By: Relevance
“…[1][2][3] This is also the first time that red blood cells have been visualized in these neovessels. From the…”
mentioning
confidence: 73%
“…[1][2][3] This is also the first time that red blood cells have been visualized in these neovessels. From the…”
mentioning
confidence: 73%
“…Human autopsy studies showed occluded channels as early as 2 days after surgery. 9,10 Few studies have shown an increase in myocardial perfusion after TMR. 12,22 Increased perfusion, when present, was not correlated with channel patency.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 However, the majority of human and experimental studies have not been able to demonstrate histologically sustained patency of the channels created. 9,10 Objective improvement in myocardial perfusion by thallium imaging studies has also been an inconsistent finding. 5,[11][12][13] Furthermore, improvement in myocardial perfusion has been documented primarily several months after TMR, whereas the improvement in angina is observed in most patients within a few days after the procedure.…”
mentioning
confidence: 99%
“…Human necropsy studies [7][8][9][10] have reported an increased capillary network within the laser channels. The factors responsible for stimulating angiogenesis after laser revascularisation have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…However, channel patency has been seriously questioned by experimental 5 6 as well as clinical data. [7][8][9] Neovascularisation induced by the laser has been suggested as a potential mechanism. Because of its potential for percutaneous application, the holmium:yttrium-aluminium garnet (holmium-YAG) laser has emerged as a promising device for laser revascularisation.…”
mentioning
confidence: 99%